First report of the genus Xerophorus from Asia with the description of Xerophorus pakistanicus (Callistosporiaceae), a new species from Southern Punjab, Pakistan - Asif, Muhammad; Saba, Malka; Raza, Mubashar (Phytotaxa, 2023)
A novel species, Xerophorus pakistanicus, has been identified from Southern Punjab, Pakistan, based on morphological characters and molecular phylogenetic analyses. Xerophorus pakistanicus is characterized by a brown to dull orange, parabolic to campanulate pileus, a stipe turning light yellowish brown on handling, an absence of an annulus, amygdaliform to oblong basidiospores, utriform to pyriform caulocystidia, and the presence of clamp connections only in the stipitipellis. A phylogram, based on the combined nrITS-28S dataset, was constructed to assess the phylogenetic position of our strain, resulted Xerophorus pakistanicus sp. nov. within the genus Xerophorus. We present the new species with an illustrated morphological description and comparison with similar morphological or phylogenetically related species. This is the first record of the genus Xerophorus from Asia. A key to the known species of Xerophorus is also provided.